2020
DOI: 10.1038/s41580-020-00315-9
|View full text |Cite|
|
Sign up to set email alerts
|

Gene regulation by long non-coding RNAs and its biological functions

Abstract: Evidence accumulated over the past decade shows that long non-coding RNAs (lncRNAs) are widely expressed and have key roles in gene regulation. Recent studies have begun to unravel how the biogenesis of lncRNAs is distinct from that of mRNAs and is linked with their specific subcellular localizations and functions. Depending on their localization and their specific interactions with DNA, RNA and proteins, lncRNAs can modulate chromatin function, regulate the assembly and function of membraneless nuclear bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
2,641
1
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,185 publications
(2,676 citation statements)
references
References 302 publications
(453 reference statements)
21
2,641
1
13
Order By: Relevance
“…Moreover, epithelial-mesenchymal transition, a prevalent process in tumors, is largely regulated by multiple lncRNAs transcriptionally or post-transcriptionally [ 84 ]. Besides, involvement of lncRNAs in regulating some key oncogenic factors such as p53 and MYC has provided evidence for their cancer-relevant functions [ 10 ]. And currently, the use of antisense oligonucleotides, small molecules for the targeting of lncRNAs, and tools based on CRISPR–Cas systems may provide new approaches for lncRNA-based targeted therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, epithelial-mesenchymal transition, a prevalent process in tumors, is largely regulated by multiple lncRNAs transcriptionally or post-transcriptionally [ 84 ]. Besides, involvement of lncRNAs in regulating some key oncogenic factors such as p53 and MYC has provided evidence for their cancer-relevant functions [ 10 ]. And currently, the use of antisense oligonucleotides, small molecules for the targeting of lncRNAs, and tools based on CRISPR–Cas systems may provide new approaches for lncRNA-based targeted therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, involvement of lncRNAs in regulating some key oncogenic factors such as p53 and MYC has provided evidence for their cancer-relevant functions [ 10 ]. And currently, the use of antisense oligonucleotides, small molecules for the targeting of lncRNAs, and tools based on CRISPR–Cas systems may provide new approaches for lncRNA-based targeted therapy [ 10 ]. However, adopting lncRNAs as the prognostic or therapeutic markers remains experimentally proposed since the lack of large sample trial to confirm their efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondently, Zhang et al, observed that the expression levels of genes regulating erythroid lineage (ε-globin, βH1-globin) and the cognate transcription factors (GATA-1/FOG-1 and KLF) were markedly reduced in UFL1 deficient fetal livers, thus assigning UFM1 a role in transcription [ 62 ]. In addition to partaking in transcriptional regulation of a variety of genes [ 92 ], the long non-coding RNAs (lncRNA) of UFC1, which are large RNA transcripts that do not encode proteins but have regulatory roles [ 92 , 93 ], have been found to critically modulate oncogene expression thus contributing to tumorigenesis, progression and metastasis, in numerous cancers [ 94 , 95 ].…”
Section: Biological Function Of Ufmylationmentioning
confidence: 99%
“…On the one hand, recent advances in RNA sequencing (RNA-seq) and computational techniques have dramatically expanded the repertoire of cellular RNAs, realizing that 80–90% of the eukaryotic genome is transcribed into RNA. Thereby, only 1–2% of the genome serves as a template for protein synthesis, while the majority of the genome is pervasively transcribed into non-coding RNAs, a large fraction of them as long non-coding RNAs (lncRNAs), which are defined as transcripts of more than 200 nucleotides without evident protein coding functionality [ 1 , 2 ]. On the other hand, bioinformatics and recent methodological advances combined with sensitive mass-spectrometry (MS) suggests that 5–10% of the cellular proteome can interact with RNA [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%